2004
DOI: 10.1097/00129492-200403000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Cerebral Oxygen Toxicity by Sound Conditioning

Abstract: Our data show that sound conditioning prolongs the latency to oxygen-induced convulsions. This effect was not accompanied by significant changes in whole-brain antioxidant enzyme activity or the magnitude of lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Animal studies indicate that the optimal timing for ITD would be about 40 minutes before Cisplatin delivery. 10,18,42,43 In the clinical realm we found it difficult to follow the ideal timing for ITD injection prior to Cisplatin treatment. This might decrease the potential maximal protective effect of Dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies indicate that the optimal timing for ITD would be about 40 minutes before Cisplatin delivery. 10,18,42,43 In the clinical realm we found it difficult to follow the ideal timing for ITD injection prior to Cisplatin treatment. This might decrease the potential maximal protective effect of Dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…This results in lipid, protein, and nucleic acids peroxidation with Caspase system activation and apoptosis of inner ear cells. 4,[10][11][12] The outer hair cells at the basal turn of the cochlea are initially lost to be followed by the remaining outer hair cells, inner hair cells, supporting cells, and spiral gangalion neurons. 13 Advanced ototoxicity damages the stria vascularis and decreases the cochlear blood supply, resulting in reduced endocochlear potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of prevention methods have been proposed, few measures have been applied to practice except controlling the pressure and duration of HBO exposure. [29][30][31][32] In earlier studies, GGA, an anti-ulcer drug, was found to increase HSP70 expression in the gastrointestinal mucosa, liver, heart, and other tissues. 33 It was reported that GGA could also induce HSP70 expression in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of prevention methods have been proposed, few measures have been applied to practice except controlling the pressure and duration of HBO exposure. 2932…”
Section: Discussionmentioning
confidence: 99%